Abuse Potential of Biased Mu Opioid Receptor Agonists. (November 2018) - Negus, S. Stevens; Freeman, Kevin B.
Abstract : G protein-biased mu opioid receptor (GPB-MOR) agonists constitute an emerging class of opioid analgesics. The first-in-class GPB-MOR agonist TRV130 (oliceridine) produces typical opioid-like abuse-related effects in rodents and humans. Although GPB-MOR agonists may be safer than conventional opioids on some endpoints, prevailing evidence suggests that they will retain opioid-like abuse potential.